Tuning the reactivity of alkoxyl radicals from 1,5-hydrogen atom transfer to 1,2-silyl transfer - Zhaoliang Yang (Nature Portfolio, 2021)
The generation of α-carbon radicals from alkoxyl radicals is challenging because 1,2-hydrogen atom transfer (HAT) is usually less favoured than 1,5-HAT. Here, the authors report a strategy to inhibit 1,5-HAT by introducing a silyl group into the α-position of alkoxyl radicals, enabling preparation of α-alkoxylimino alcohols and α-heteroaryl alcohols.